2021
DOI: 10.1371/journal.pone.0259158
|View full text |Cite
|
Sign up to set email alerts
|

B cell activating factor (BAFF) from neutrophils and dendritic cells is required for protective B cell responses against Salmonella typhimurium infection

Abstract: Mice lacking B cells are more susceptible to S. typhimurium infection. How B cells contribute to protective immunity against Salmonella and what signals drive their activation are still unclear. Neutrophils (Nphs), monocytes (MOs), and dendritic cells (DCs) are involved in early immune responses to control the initial replication of S. typhimurium. These cells can produce B cell activating factor (BAFF) required for mature B cell survival and may help regulate B cell responses during Salmonella infection. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…TI responses by marginal zone B cells in the spleen can also be induced in both a contact‐dependent and contact‐independent manner by a broad range of innate cells, including neutrophils, 17 dendritic cells (DCs) 18 and mast cells. 19 These innate ‘B helper cells’ have been shown to be important (in mice) for protection from a range of pathogens including S typhimurium 20 and West Nile Virus. 21 The reliance on innate cells in these responses has led to the proposal that they may constitute a “TI‐3” response distinct from TI type 1 and TI type 2 responses.…”
Section: B Cell Subsets and Activationmentioning
confidence: 99%
“…TI responses by marginal zone B cells in the spleen can also be induced in both a contact‐dependent and contact‐independent manner by a broad range of innate cells, including neutrophils, 17 dendritic cells (DCs) 18 and mast cells. 19 These innate ‘B helper cells’ have been shown to be important (in mice) for protection from a range of pathogens including S typhimurium 20 and West Nile Virus. 21 The reliance on innate cells in these responses has led to the proposal that they may constitute a “TI‐3” response distinct from TI type 1 and TI type 2 responses.…”
Section: B Cell Subsets and Activationmentioning
confidence: 99%
“…In contrast to the TLR7 Tg mice, splenic Nphs from BAFF-RFP Sle1 mice had lower BAFF expression per cell than Nphs from BAFF-RFP controls (Figures 3A, B), possibly due to Nph activation. Indeed, we and others have shown that upon activation, Nphs not only release BAFF from the intracellular stores but also down-regulate BAFF expression (11). cDC-and B cell-BAFF expression per cell did not change in the spleens of Sle1 autoimmune mice (Figure 3B).…”
Section: Regulation Of Baff-rfp Expression In Splenic and Bm Myeloid ...mentioning
confidence: 77%
“…Heterozygous BAFF-RFP +/-(BAFF-RFP) mice express lower BAFF levels, as one Baff allele expresses the RFP protein as a measurement of BAFF expression and the other allele expresses wild-type (WT) Baff (10, 11). However, BAFF-RFP still retain a reduced population of mature B cells, and thus can be used for functional studies of B cells and Ab responses (10,11). We first assessed how either the Tlr7.1 Tg or the Sle1 background affected serum BAFF levels.…”
Section: Induction Of Baff Autoantibodies and Plasma Cells In Baff-rf...mentioning
confidence: 99%
See 2 more Smart Citations